Bioavailability of phosphorus in selected feedstuffs for pigs - Huang, K.; Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We used 140 crossbred pigs averaging 30.4 lb to determine phosphorus bioavailability with the slope-ratio technique. A standard curve was established by feeding a basal diet 0% inorganic phosphorus and three levels of NaH2P04H20 (.056% P, .112% P, and .168% P). The response curve of test ingredients waS established with basal diet data and feeding three levels of each test ingredient. The test ingredient was incorporated at the expense of dextrose. The relative phosphorus bioavailability values were: 51% for wheat, 23% for milo, 35% for oats, 29% for corn, 36% for soybean meal, 42% for cottonseed meal, 93% for meat and bone meal, and 102% for dicalcium phosphate.
Keywords: Swine; Phosphorus; Selected feedstuff; Bioavailability